Mobile phone adoption and appropriation among the Malaysian teenagers: the influence of intrinsic and extrinsic motivation - Nor, Shahriza Abdul Karim; Norshidah, Mohamed; Ramlah Hussein, * (2011)
Given the significant impact the wireless technologies provided to date, not many research can be found conducted in understanding the pattern of wireless use and adoption among various cohorts of the Malaysian population particularly those of teenagers. This research conducted in order to find out about the pattern of wireless technologies? adoption and use among the Malaysian teenagers. Subsequently, this study expects to establish an understanding of the usage pattern based on the intrinsic and extrinsic motivations theory and the adoption?appropriation of technology perspective. This study should provide a very important contribution to the understanding of teenagers and their mobile phone use behavior. At the same time, this study can also assist in policy development of wireless phone application among high school students and allows for respective authority to re-think of how to exploit the technology to benefit the teenagers for the purpose of learning and motivation. In addition, the findings may also contribute to the modeling of mobile phone use as a strategy to match mobile phone design to user?s technological needs and expectations.